A novel bipolar host material based on carbazole and 1, 3, 5-triazine with an extremely low efficiency roll-off for green PhOLEDs. (December 2021) - Qu, Wenshan; Gao, Zhixiang; Li, Wei; Fan, Xiaxia; Shi, Yunlong; Miao, Yanqin; Yu, Guichen; Zhou, Haitao; Huang, Jinhai; Wang, Hua
Abstract: In this contribution, a novel bipolar host material, namely CzTrz, consisting of a phenylcarbazole for hole transport and a diphenyltriazine for electron transport, was synthesized and investigated. Besides, a carbazole-based unipolar host BCz2 was designed as a reference. Both CzTrz and BCz2 display good thermal stability, high triplet energy level ( E T ) and suitable frontier orbital levels. Green PhOLEDs hosted by CzTrz and BCz2 show turn-on voltage ( V on ) of 3.5 and 3.8 V, maximum luminance ( L max ) of 30, 280 and 35, 050 cd m −2, and maximum external quantum efficiency ( EQE max ) of 15.49 and 11.84%, respectively. Remarkably, the CzTrz -based device reveals an extremely low efficiency roll-off at the high luminance, for example, 15.35% at 1000 cd m −2 and 13.85% at 5000 cd m −2, corresponding to merely 0.9% and 10.6% roll-off percentage, which is among the best results ever reported as green bipolar hosts. Graphical abstract: Image 1 Highlights: A novel bipolar host material (CzTrz ) based on phenylcarbazole and diphenyltriazine was designed and synthesized. CzTrz exhibits good thermal stability, prominent bipolar features, appropriate HOMO/LUMO and high triplet energy levels. The CzTrz -hosted green device shows an extremely low efficiency roll-off (0.9%) at the luminance of 1000 cd m −2 .